Benefits of being bilingual? The relationship between pupils' perceptions of teachers' appreciation of their home language and executive functioning. (December 2016) - Goriot, Claire; Denessen, Eddie; Bakker, Joep; Droop, Mienke
Aims: We aimed to investigate whether bilingual pupil's perceptions of teachers' appreciation of their home language were of influence on bilingual cognitive advantages. Design: We examined whether Dutch bilingual primary school pupils who speak either German or Turkish at home differed in perceptions of their teacher's appreciation of their HL, and whether these differences could explain differences between the two groups in executive functioning. Data and analysis: Executive functioning was measured through computer tasks, and perceived home language appreciation through orally administered questionnaires. The relationship between the two was assessed with regression analyses. Findings: German-Dutch pupils perceived there to be more appreciation of their home language from their teacher than Turkish-Dutch pupils. This difference did partly explain differences in executive functioning. Besides, we replicated bilingual advantages in nonverbal working memory and switching, but not in verbal working memory or inhibition. Originality and significance: This study demonstrates that bilingual advantages cannot be dissociated from the influence of the sociolinguistic context of the classroom. Thereby, it stresses the importance of culturally responsive teaching.